Perkawinan Turun Ranjang Dalam Perspektif Hukum Keluarga Islam - Aziz Basuki; A. Kumedi Ja’far (Jurnal Multidisiplin Indonesia, 2024)
Bed-step marriage is a tradition that still thrives in several cultures, where a man, usually the younger brother of the deceased husband, marries the deceased's wife to maintain the integrity of the family. Although this tradition is considered an effort to maintain the honor and stability of the family, this practice raises a number of questions from an Islamic legal perspective. This paper aims to examine the phenomenon of bed-step marriage from an Islamic legal perspective, focusing on the requirements for a valid marriage, women's rights, the principle of justice in inheritance, and the purpose of marriage in Islam. Based on a literature review and analysis of sharia arguments, it was found that although Islamic law does not explicitly prohibit marriage with the husband's younger brother after the 'iddah period is over, this practice has the potential to conflict with the principles of consent, freedom to choose a partner, and justice in inheritance if carried out on the basis of coercion or social pressure. Therefore, bed-step marriage in Islamic law is only valid if it meets the requirements that have been set, without any element of coercion, and aims to form a harmonious and loving family.